2021
DOI: 10.1111/jav.02716
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in body size and plumage colour according to diet composition in a nocturnal raptor

Abstract: Predator-prey interactions are amongst the strongest selective forces that promote the evolution of local phenotypes in both predators and prey. However, intraspecific spatial covariation in phenotypic traits between predators and prey has been rarely investigated, especially at a large geographic scale. Here, we studied the covariation between prey composition and some phenotypic traits, such as wing length, bill length and plumage colour, of a widely-distributed nocturnal predator, the western barn owl Tyto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…These results emphasise the potential link between phenotypic variation and the local adaptation of the barn owl. A previous study identified a significantly positive relationship between body size and the hunted prey size, suggesting that larger owls might be more competitive in hunting larger prey (Romano et al 2021). (Romano et al 2020) also highlighted a significant geographical and climatic trend in the diet of this raptor species, with an increase in the proportion of small prey in the diet of colder environments (including Central and Northern Europe).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results emphasise the potential link between phenotypic variation and the local adaptation of the barn owl. A previous study identified a significantly positive relationship between body size and the hunted prey size, suggesting that larger owls might be more competitive in hunting larger prey (Romano et al 2021). (Romano et al 2020) also highlighted a significant geographical and climatic trend in the diet of this raptor species, with an increase in the proportion of small prey in the diet of colder environments (including Central and Northern Europe).…”
Section: Discussionmentioning
confidence: 95%
“…(Romano et al 2020) also highlighted a significant geographical and climatic trend in the diet of this raptor species, with an increase in the proportion of small prey in the diet of colder environments (including Central and Northern Europe). Finally, this variation in body size also co-varies with colour polymorphism (with smaller owls being redder, (Romano et al 2021), a trait known to be maintained by selection (Antoniazza et al 2010), and linked to hunting behaviour (Roulin 2004; Romano et al 2021). Taken together, these results suggest an association between the size of the barn owl, their colour, their behaviour and their diet, all possibly linked to the local adaptation of the barn owl to heterogeneous climatic conditions in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded information on plumage colour of thousands of barn owl skins collected by several museums and private citizens (see Romano et al, 2020Romano et al, , 2021aRomano et al, , 2021bRomano, Séchaud, et al, 2019).…”
Section: Museum Skin Collection and Their Insular Originmentioning
confidence: 99%
“…This categorization was used in several previous studies (e.g. Romano et al, 2021aRomano et al, , 2021bRomano, Séchaud, et al, 2019;Roulin et al, 2018) and has been shown to be highly correlated with reflectance in the visible light when compared to spectrophotometric measures (Dreiss & Roulin, 2010). Moreover, this categorization is correlated with pheomelanin, but not eumelanin (Roulin et al, 2008), thus indicating that it is a good proxy of pheomelanin content.…”
Section: Museum Skin Collection and Their Insular Originmentioning
confidence: 99%
See 1 more Smart Citation